Growth mindset, Grit, and Academic Self-efficacy as determinants of Academic Performance in Peruvian university students - Correa-Rojas, Jossué (2024)
Currently, the study of non-cognitive variables and their effect on the academic performance of students has gained relevance. In view of that, the purpose of the present study was to analyze through structural equation modeling to what extent growth mindset, self-efficacy, and grit have direct effects on student performance. For this, an explanatory design of latent variables was followed, in which 305 university students participated, including men (41.8%) and women (58.2%), who reported an average age of 22.8 (SD = 3.5), all included due to convenience. To measure the independent variables, the ITIS (growth mindset), Grit-S (tenacity) and EPAESA (academic self-efficacy) were applied, while for the measurement of the dependent variable, the grades of the students of the two last semesters were used. Among the main findings, it is reported that growth mindset, grit, and self-efficacy have direct and significant effects on the academic performance of students. In conclusion, this set of non-cognitive variables successfully explains the academic performance of the study participants.